Asymmetries of Spatial Contestations: Controlling Protest Spaces and Coalition-Building during the Iranian December 2017 Protests. Issue 1 (1st June 2020) - Sydiq, Tareq
Abstract: Based on fieldwork carried out from 2017 and 2018, this article examines various attempts to both organize publicly and disrupt such attempts during the Iranian protests during that time. It argues that interference with spatial realities influenced the social coalitions built during the protests, impacting the capacity of actors to build such coalitions. The post-2009 adaptation of the state inhibited cross-class coalitions despite being challenged, while actors used spatial phrasing indicating they perceived spatial divisions to emulate political ones. Meanwhile, in the immediate aftermath of the December 2017 protests, further attempts to control protest actions impacted not only those who would be able to participate in such events in the future, but also those who felt represented by them and who would be likely to sympathize with them. Based on the spatial conditions under which coalitions form, I argue that asymmetrical contestations of spatiality determined the outcome of the December 2017 protests and may contribute to an understanding of how alliances in Iran will form in the future.